Effects of a Dehydroevodiamine-Derivative on Synaptic Destabilization and Memory Impairment in the 5xFAD, Alzheimer's Disease Mouse Model - Kang, Shinwoo; Ha, Sungji; Park, Hyunjun; Nam, Eunjoo; Suh, Won Hyuk; Suh, Yoo-Hun; Chang, Keun-A (Frontiers in Behavioral Neuroscience, 2018)
The carboxy-DHED (cx-DHED) is a derivative of DHED which improves memory impairment. Carboxyl modification increases solubility in water, indicating that its bioavailability is higher than those of DHED. cx-DHED is expected to have better therapeutic effects on Alzheimer's disease than those of DHED. In this study, we investigated the therapeutic effects of cx-DHED and underlying mechanism in 5xFAD AD model mice. In several behavioral tests such as the Y-maze, passive avoidance, and Morris water maze test, memory deficits improved significantly in cx-DHED-treated Tg mice compared with those in vehicle-treated Tg mice. We also found that AD-related pathologies, including amyloid plaque deposition and tau phosphorylation, were reduced after the cx-DHED treatment of Tg mice. We determined levels of synaptic proteins such as GluN1, GluN2A, GluN2B, PSD-95 and Rabphilin3A, and Rab3A in the brains of each group and found that GluN2A and PSD-95 significantly increased in cx-DHED-treated Tg mice brains compared with those in Tg-vehicle mice brains. These results suggest that cx-DHED has therapeutic effects on 5xFAD AD model mice through the improvement of synaptic stabilization.